2004
DOI: 10.1093/jee/97.6.1912
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Activities of Extracts of Stellera chamaejasme Against Tetranychus viennensis (Acari: Tetranychidae)

Abstract: Extracts of a perennial and poisonous weed, Stellera chamaejasme L. (Thymelaeaceae) were bioassayed to determine their acaricidal activities against Tetranychus viennensis Zacher (Acari: Tetranychidae) in the laboratory. Extracts had both contact and systemic toxicity to the mite. After liquid chromatography and thin layer chromatography, the extract was further concentrated, separated, and bioassayed. This study is the first to report the acaricidal property of S. chamaejasme and its potential as a botanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Compositae) and Tanacetum vulgare Linné were toxic to the twospotted spider mite, Tetranychus urticae Koch (Chiasson et al 2001). Extracts from Azadirachta indica A. Juss and Stellera chamaejasma L. have strong acaricidal activity (Sundaram and Sloane 1995, Williams and Mansingh 1996, Shi et al 2004. Erler and Tunç (2005) tested eight monoterpenoids from plant essential oils for bioactivity to T. cinnabarinus.…”
Section: Abstract Green Walnut Husks Methyl Palmitate Acaricidal Amentioning
confidence: 99%
“…Compositae) and Tanacetum vulgare Linné were toxic to the twospotted spider mite, Tetranychus urticae Koch (Chiasson et al 2001). Extracts from Azadirachta indica A. Juss and Stellera chamaejasma L. have strong acaricidal activity (Sundaram and Sloane 1995, Williams and Mansingh 1996, Shi et al 2004. Erler and Tunç (2005) tested eight monoterpenoids from plant essential oils for bioactivity to T. cinnabarinus.…”
Section: Abstract Green Walnut Husks Methyl Palmitate Acaricidal Amentioning
confidence: 99%
“…Different root extracts of Stellera chamaejasme showed antimicrobial activity against several microorganisms, and particularly against three bacteria, and twelve phytopathogenic fungi (Lin et al 2009;Bai et al 2012). Other studies have reported pesticidal and acaricidal activity (Wang et al 2002;Shi et al 2004). Daphne bholua is used to treat intestinal worms in Sikkim Himalaya (Panda and Misra 2010: 186), it showed antibacterial, antifungal, antiprotozoal, and antiviral activity (Goel et al 2002).…”
Section: Recent Researchmentioning
confidence: 99%
“…Supporting information available online at http://www.thieme-connect.de/ejournals/toc/plantamedica Stellera chamaejasme L. (Thymelaeaceae) is a toxic perennial herb. Its root is known as Langdu and is described in the Chinese Pharmacopoeia [1] as having antiviral [2,3], antitumor [4], antibacterial [5], immunomodulatory [6], and insecticidal effects [7,8]. The use of Langdu along with various clinically prescribed drugs may result in a herb-drug interaction or Langdu toxicity [9].…”
Section: Intmentioning
confidence: 99%
“…The incubation conditions were similar to those used with HLMs except that the CYP content was 50 pmol CYP×mL −1 or the UGT concentration was 0.5 mg protein × mL −1 . Eleven concentrations of chamaechromone (2,5,10,25,50,100,200, 500, 750, 1000, and 2000 µM) were incubated in triplicate with HLM samples, hCYPs, or hUGTs to obtain the kinetic profiles of chamaechromone metabolism. Quantitative analysis via LC-MS was performed as described previously [12].…”
mentioning
confidence: 99%